Recent progress of photocatalysts based on tungsten and related metals for nitrogen reduction to ammonia - Hui, Xiangchao; Wang, Lijun; Yao, Zhibo; Hao, Leiduan; Sun, Zhenyu (Frontiers in Chemistry, 2022)
Photocatalytic nitrogen reduction reaction (NRR) to ammonia holds a great promise for substituting the traditional energy-intensive Haber–Bosch process, which entails sunlight as an inexhaustible resource and water as a hydrogen source under mild conditions. Remarkable progress has been achieved regarding the activation and solar conversion of N2 to NH3 with the rapid development of emerging photocatalysts, but it still suffers from low efficiency. Unfortunately, a comprehensive review on photocatalysts covering tungsten and related metals as well as their broad ranges of alloys and compounds is lacking. This review aims to summarize recent advances in this regard, focusing on strategies to enhance the photocatalytic performance of tungsten and related metal semiconductors for the NRR. The fundamentals of solar-to-NH3 photocatalysis, reaction pathways, and NH3 quantification methods are presented, and the concomitant challenges are also revealed. Finally, we cast insights into the future development of sustainable ammonia production, and highlight some potential directions for further research in this vibrant field.